Increasing Electric Vehicle Penetration Using Smart Switching and Emergency Uprating - Liu, Shuran; Cheng, Meng; Xing, Qinhao; Jiang, Yizhe; Xiang, Qianliang; Xie, Hailian (Frontiers in Energy Research, 2021)
One of the key challenges facing distribution network operators today is the expected increase in electric vehicles. The increased load from EV charging will result in distribution assets becoming 'thermally overloaded' due to higher operating temperatures. In addition to the issue of increased load, we have a limited understanding of the behavior and performance of the distribution assets and their potential to accept the increased load. It has been well acknowledged that EVs increase the network loading level, leading to a reduced system reliability performance. These results have not been quantified in a realistic case study, including actual cable rating and design properties. To address this gap, this paper proposes a novel methodology in the existing power network reliability evaluation framework, which quantifies the impact of different EV penetration levels on distribution network reliability, and the thermal performance of distribution cables. Novel approaches using smart switching technology and emergency uprating are proposed to reduce the peak power demand caused by EVs, in order to reinforce the reliability of the grid and to boost the maximum allowable EV penetration in the distribution networks. The methodology was applied using a case study on the modified EV-integrated RBTS bus 4 distribution network. The results showed that the negative impact of EVs on network performance can be mitigated by the implementation of smart switching technology. The peak demand under contingencies can also be accepted by the cables though emergency uprating. The frequency and duration of EV demand interruption was also significantly reduced. Thus, a higher EV penetration can be accommodated.